Microsoft 365 Digital Classroom Tools and the Development of English Teachers’ Self-Efficacy in ICT - Ro’ifah; Febriana, Astri Dewi; Saiful , Jepri Ali (Universitas Nusantara PGRI Kediri, 2022)
Present scholarship informs that teacher self-efficacy is in nexus with the quality of teaching. Thus, this study considers the issue of teacher self-efficacy in English teaching, particularly concerning ICT. It aimed at examining whether the English teachers’ self-efficacy in ICT can be developed by using effective strategies of Microsoft 365 digital classroom tools in teaching English. The study employed a mix-method analysis with a congruent mixed-method design. The participants were three female and one male English teachers teaching English in elementary schools. They all received educational intervention on the practical strategies of using Microsoft 365 digital classroom tools. Closed-ended questionnaire was used to get quantitative data and it was administered before and after the teachers received the intervention. The data from the questionnaire were analyzed quantitatively through mean comparison. Besides, an interview was used to get qualitative data which were analyzed thematically. The quantitative result showed the mean comparison between pre and post-test: the post-test mean score was higher (M = 3.18) than pre-test (M = 2.71). The qualitative data indicated that the participants’ efficacy for instructional strategies, classroom management, and student engagement were getting better. In short, both quantitative and qualitative showcase that the self-efficacy of the teachers in ICT was developed when they implemented the Microsoft 365 Digital Classroom Tools. Keywords: English language teaching, ICT, Microsoft 365, teacher self-efficacy